2011
DOI: 10.1088/2041-8205/740/1/l13
|View full text |Cite
|
Sign up to set email alerts
|

A Variable Mid-Infrared Synchrotron Break Associated With the Compact Jet in Gx 339-4

Abstract: Many X-ray binaries remain undetected in the mid-infrared, a regime where emission from their compact jets is likely to dominate. Here, we report the detection of the black hole binary GX 339-4 with the Widefield Infrared Survey Explorer (WISE) during a very bright, hard accretion state in 2010. Combined with a rich contemporaneous multiwavelength dataset, clear spectral curvature is found in the infrared, associated with the peak flux density expected from the compact jet. An optically-thin slope of ∼-0.7 and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
220
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(245 citation statements)
references
References 45 publications
24
220
1
Order By: Relevance
“…We do not see evidence of a non-thermal power-law break at frequencies lower than the J band, suggesting that the break is located at frequencies greater than or equal to the J band. This is in agreement with Coriat et al (2009) but contrary to what was observed by Gandhi et al (2011). During 2010 when GX 339-4 was once again very bright during the hard state (V = 14.74 mag) Gandhi et al (2011) found the power-law break to be located in the mid-IR.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We do not see evidence of a non-thermal power-law break at frequencies lower than the J band, suggesting that the break is located at frequencies greater than or equal to the J band. This is in agreement with Coriat et al (2009) but contrary to what was observed by Gandhi et al (2011). During 2010 when GX 339-4 was once again very bright during the hard state (V = 14.74 mag) Gandhi et al (2011) found the power-law break to be located in the mid-IR.…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with Coriat et al (2009) but contrary to what was observed by Gandhi et al (2011). During 2010 when GX 339-4 was once again very bright during the hard state (V = 14.74 mag) Gandhi et al (2011) found the power-law break to be located in the mid-IR. They fit a power law to the radio-W4 data with a slope of +0.29 ± 0.02, significantly higher than slopes found in this paper and others.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Malzac 2014), and we are here probing slower timescales than this, in which case on these slow timescales the longer wavelengths may have more rms variability power than the shorter wavelengths, as observed between KS and J-bands. This may be consistent with the results of Gandhi et al (2011), who found that in GX 339-4, at wavelengths close to the jet spectral break the rms variability was of high amplitude, but the variations were slow, with smooth changes on timescales of minutes-hours. We therefore consider both options, optically thin and optically thick synchrotron, are plausible possibilities for the origin of the NIR spectrum and variability.…”
Section: Swift J13572-0933supporting
confidence: 92%
“…This is exactly what one can expect when a source undergoes an LHS to HSS spectral transition: the colour changed and thermal processes started to dominate. During the rising LHS, Gandhi et al (2011) found that the jet spectrum was highly variable in the mid-IR. The break between optically thick (self-absorbed) and optically thin synchrotron emission in the jet spectrum was found to vary between ∼3.6 and 22 μm on timescales of minutes-hours.…”
Section: Spectral Energy Distributionsmentioning
confidence: 99%